Simulation of CZTSSe thin-film solar cells in COMSOL: three-dimensional optical, electrical, and thermal models - Zandi, Soma; Saxena, Prateek; Razaghi, Mohammad; Gorji, Nima E. (IEEE, 2020)
The Cu $_2$ ZnSnS $_x$ Se $_{4-x}$ (CZTSSe) thin-film solar cells have attracted the attention of researchers due to its earth-abundant composition containing Copper, Zinc, Tin and Sulfur, and Selenide with 12.6% record efficiency (2013-IBM). A 3-D simulation analysis is presented here on the optical, electrical, and thermal characteristics of CZTSSe solar cell using COMSOL multiphysics 3-D simulation package. COMSOL is capable of calculating the optical–electrical–thermal models through electromagnetic wave, semiconductor, and heat transfer modules for a finely meshed structure. Using this capability, we have calculated the optical photogeneration rate of the a Mo/Mo(S,Se) $_2$ /CZTSSe/CdS/ZnO/ITO/air structure by inserting the refractive index and extinction coefficient of every layer in Wave optic module in COMSOL. We also calculated the total optical generation rate for two structures with and without Mo(S,Se) $_2$ layer at the junction of Mo and CZTSSe layers. The current–voltage curve, electric field profile, and the recombination rate of the cell has also been calculated by Semiconductor module coupled to wave optic module. The current–voltage characteristics show an improvement in $V_{\text{oc}}$ for the cell with Mo(S,Se) $_2$ layer (0.46 to 0.513 V) which was also suggested by IBM for a record cell efficiency. Finally, the thermal maps of the cell has been calculated by heat transfer module coupled to semiconductor module considering the Shockley–Read–Hall (SRH) recombination heat, Joule Heat, and conductive heat flux. The total heat flux magnitude of the cell was also mapped as a result out of these heat generation and cooling sources. The SRH heat is maximum within the depletion width at the CZTSSe/CdS interface, whereas the Joule heating is intensive at the Mo/Mo(S,Se) $_2$ /CZTSSe side. Interesting is to see that the heat is mainly conducted to environment from Mo side presented by the conductive heat map. The total heat flux is intensive at both top and bottom interfaces which means the heat is generated at both top and bottom sides of the cells and not only from the illuminated part
Keywords: thin films; 3-D simulation; solar cell; COMSOL; CZTSSe